2009
DOI: 10.1007/s12262-009-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of difficult lap chole: a scoring method

Abstract: Background Laparoscopic cholecystectomy (LC) has become the procedure of choice for management of symptomatic gallstone disease. At times it is easy and can be done quickly. Occasionally it is diffi cult and takes longer time. But there is no scoring system available to predict the degree of diffi culty of LC preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
146
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(196 citation statements)
references
References 11 publications
(11 reference statements)
21
146
5
1
Order By: Relevance
“…Low risk patients could be identified and appropriately scheduled in an ambulatory care facility, and selected as training cases for surgical trainees, 9 whilst high risk patients should be appropriately counselled and operated by experienced surgeons. The majority of studies that have evaluated risk factors for conversion to open cholecystectomy are small retrospective series or population-based databases [1][2][3][4]6,7,[10][11][12][13][14] (Table 1). Several studies have developed risk scores, but their clinical utility is limited by retrospective data, small sample sizes and/or lack of validation.…”
Section: Introductionmentioning
confidence: 99%
“…Low risk patients could be identified and appropriately scheduled in an ambulatory care facility, and selected as training cases for surgical trainees, 9 whilst high risk patients should be appropriately counselled and operated by experienced surgeons. The majority of studies that have evaluated risk factors for conversion to open cholecystectomy are small retrospective series or population-based databases [1][2][3][4]6,7,[10][11][12][13][14] (Table 1). Several studies have developed risk scores, but their clinical utility is limited by retrospective data, small sample sizes and/or lack of validation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,6,13 An interesting observation by Randhawa et al in his study states a palpable gallbladder as a significant predictor of intraoperative difficulty. 10 This was one of the unique predictive factor identified by the author. Patil et al too reiterated this in his study where a statistical significance was observed with this variable.…”
Section: Clinical Parameters-disease Factorsmentioning
confidence: 91%
“…9 Genc V et al and Randhawa et al did not find any statistical significance for previous abdominal surgery in prediction of difficult lap cholecystectomy. 6,10 This was attributed to experience of authors in adhesiolysis.…”
Section: History Of Previous Surgeriesmentioning
confidence: 98%
See 1 more Smart Citation
“…Dear Editor, I read with interest the recent article on: Preoperative prediction of difficult lap chole: a scoring method [1].…”
mentioning
confidence: 99%